Electrochemical Degradation of Atrazine in Aqueous Solution at a Platinum Electrode - Mamián,M. (2009)
Atrazine is a highly used herbicide and it has been found in both deep and superficial waters. Its solubility in water is reduced and is relatively stable in humid environments, where it has a half-life of one hundred days. Atrazine can be degraded by oxidative photolysis or by microorganisms. It is moderately toxic in humans, animals and plants, because it can be absorbed by inhalation, ingestion or through the skin. In this work, we study the degradation of atrazine in aqueous solution using current controlled electrolysis at a platinum electrode. The effects of pH, current magnitude and direction, and temperature, were evaluated. The atrazine decomposition was monitored during electrolysis by UV-Vis spectrophotometry; quantification of atrazine was done by GC/MS, and quantification of cyanuric acid was done by HPLC. It was found that at 25 ºC in acid media, atrazine is degraded partially to cyanuric acid with formation of persistent intermediate compounds, but at 60 ºC atrazine is completely degraded to cyanuric acid. The TOC results indicate no electrochemical combustion and no mineralization was observed under the experimental conditions studied.